Pengembangan Ekonomi Syariah terhadap Potensi Pariwisata Besar oleh Bank Indonesia - Fatimatuz Zuhro (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2019)
Management of a large tourism industry based on sharia economy is one of the breakthroughs that attracts the attention of financial institutions to promote economic growth equally. Economic resources that must be supported by financial institutions to maintain economic equality are the trade, textile, electronics, agriculture and large tourism sectors. With that, without the support of Islamic financial institutions will not be implemented stable and equitable economic growth. The purpose of this research is to support the distribution of Islamic economics to the industrial sector which can create economic growth and maintain the stability of public financial inflation. The research method used by the author uses qualitative methods or literature research studies with the Indonesian Banking system approach to solving Islamic financial problems. The results of this study indicate that the development of the sharia economy to the industry's large tourism potential can be a development in opening access to economic growth and can create an increase in sharia-based economy and can maintain national financial inflation.